Finite Element Analysis on Shear Strengthened Reinforced Concrete Beam with Different Orientations of Carbon Fibre Reinforced Polymer (CFRP) - Selvam, Rishitaran Pannir; Hashim, N A; Yakin, H N (Advanced and Sustainable Technologies (ASET), 2026)
Shear failure in reinforced concrete (RC) beams is a critical structural issue that can lead to sudden, catastrophic collapse. Carbon fibre reinforced polymer (CFRP) sheets have emerged as an effective retrofitting material due to their high strength-to-weight ratio, corrosion resistance, and ease of application. However, the influence of CFRP wrapping angles on shear performance remains insufficiently explored. This study investigates the impact of varying CFRP wrapping angles on the structural behaviour of RC beams to optimize shear strengthening. Using finite element analysis (FEA) in ABAQUS software, eight RC beam specimens with CFRP wrapping angles of 30°, 35°, 40°, 45°, 50°, 55°, 60°, and 90° were analysed under four-point bending. Key metrics, including shear capacity, stress distribution, and tensile stress, were evaluated. Results demonstrated that mid-range wrapping angles, particularly 35°, 40°, and 60°, significantly enhanced shear capacity and shifted failure modes from brittle to ductile, improving structural resilience. Detailed stress and deformation analyses revealed the mechanics of CFRP-strengthened beams, emphasizing the transformative impact of optimizing wrapping angle. This research addresses a critical gap in the literature and offers actionable insights to optimize CFRP retrofitting strategies. The findings contribute to enhancing the durability, safety, and sustainability of RC structures, offering a robust framework for modern structural rehabilitation (SDG 9) and sustainable construction practices (SDG 11).